Numerical Laser Energy Deposition on Supersonic Cavity Flow and Sensor Placement Strategies to Control the Flow - Ibrahim Yilmaz; Selin Aradag (The Scientific World Journal)
In this study, the impact of laser energy deposition on pressure oscillations and relative sound pressure levels (SPL) in an open supersonic cavity flow is investigated. Laser energy with a magnitude of 100 mJ is deposited on the flow just above the cavity leading edge and up to 7 dB of reduction is obtained in the SPL values along the cavity back wall. Additionally, proper orthogonal decomposition (POD) method is applied to the x-velocity data obtained as a result of computational fluid dynamics simulations of the flow with laser energy deposition. Laser is numerically modeled using a spherically symmetric temperature distribution. By using the POD results, the effects of laser energy on the flow mechanism are presented. A one-dimensional POD methodology is applied to the surface pressure data to obtain critical locations for the placement of sensors for real time flow control applications.